The Effects of Hygrothermal Conditions on the Dynamic Response of Shear Deformable Laminated Plates Resting on Elastic Foundations - Hui-Shen Shen; Jian-Jun Zheng; Xiao-Lin Huang
The effect of hygrothermal conditions on the dynamic response of shear deformable laminated plates resting on a two-parameter (Pasternak-type)elastic foundation is investigated using a micro-to-macromechanical analytical model. The material properties of the composite are affected by the variation of temperature and moisture, and are based on a micromechanical model of a laminate. The governing equations are based on higher order shear deformation plate theory and include the plate-foundation interaction and hygrothermal effects. All four edges of the plate are assumed to be simply supported with no in-plane displacements. Analytical solutions of dynamic response for symmetric cross-ply and antisymmetric angle-ply laminated plates subjected to a transverse dynamic load under different sets of hygrothermal environmental conditions are obtained by using the state variable approach. The numerical illustrations concern the free vibration and dynamic response of shear deformable laminated plates resting on Pasternak-type elastic foundations with the Winkler elastic foundations being a limiting case. The influences played by temperature rise, the degree of moisture concentration, fiber volume fraction and foundation stiffness are studied. The results show that the hygrothermal environment has a significant effect on the natural frequency as well as dynamic response of the plate.
Keywords: HYGROTHERMAL EFFECT; TRANSIENT RESPONSE; SHEAR DEFORMABLE LAMINATED PLATE; ELASTIC FOUNDATION; HIGHER ORDER SHEAR DEFORMATION PLATE THEORY